Disaster Risk Management in Shelter in RIMAC district - Espinoza Campos, Eric (2019)
In 2016, the MDR approve Rehabilitation Plan for Disaster Risk in Rimac district. -In 2016, there is a fire in the community of Cantagallo in the district of Rimac. 300 families of the Shipibo-Coniba community are affected, who receive the support from the Municipality of Rimac and the Metropolitan Municipality of Lima. -The Disaster Risk Management employees in Rimac district spend five years to elaborate a rehabilitation plan. This harmful event happened in a three-month short-time. -The post-disaster stage in this case has shown the difficulty of helping a number of citizen in the district of RIMAC. The issue is the location of public spaces to relocate people, because it has had to occupy a space in the so-called MARTINETI field in the district of Cercado de Lima that is to find a solution in another district. This is only part of the problem. The coordination of the officials of a district municipality with the metropolitan municipality of Lima is a serious factor. A help factor is that those affected are from a cultural community, this factor has facilitated understanding between the authorities and the affected population. -The current situation for shelter areas requires a real management for qualified professionals.